2016
DOI: 10.1128/aac.02975-15
|View full text |Cite
|
Sign up to set email alerts
|

The Redox Cycler Plasmodione Is a Fast-Acting Antimalarial Lead Compound with Pronounced Activity against Sexual and Early Asexual Blood-Stage Parasites

Abstract: Previously, we presented the chemical design of a promising series of antimalarial agents, 3-[substituted-benzyl]-menadiones, with potent in vitro and in vivo activities. Ongoing studies on the mode of action of antimalarial 3-[substituted-benzyl]-menadiones revealed that these agents disturb the redox balance of the parasitized erythrocyte by acting as redox cyclers-a strategy that is broadly recognized for the development of new antimalarial agents. Here we report a detailed parasitological characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 71 publications
0
35
0
Order By: Relevance
“…Evidence from neuroscience points out that conflict detection and resolution occurs extremely early in decision making (see, e.g., Achtziger et al, 2014 ) and hence should have a moderate effect in response times of large magnitude. In Achtziger and Alós-Ferrer ( 2014 ), decisions where a reinforcement heuristic had been shut down were observed to be significantly slower (and error rates significantly lower) than decisions where the heuristic was active. On the basis of this evidence, we formulate the following hypothesis.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Evidence from neuroscience points out that conflict detection and resolution occurs extremely early in decision making (see, e.g., Achtziger et al, 2014 ) and hence should have a moderate effect in response times of large magnitude. In Achtziger and Alós-Ferrer ( 2014 ), decisions where a reinforcement heuristic had been shut down were observed to be significantly slower (and error rates significantly lower) than decisions where the heuristic was active. On the basis of this evidence, we formulate the following hypothesis.…”
Section: Methodsmentioning
confidence: 96%
“…For instance, Achtziger and Alós-Ferrer ( 2014 ) study a paradigm where a reinforcement-based heuristic can conflict or be aligned with more rational decision making (optimization based on Bayesian updating of beliefs). The main predictions of the study (following the Dual-Process Diffusion Model, Alós-Ferrer, 2016 ) concern the relative speed of errors and correct responses for a given individual , i.e., a within-participant comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Artemisinin or one of its synthetic derivatives constitutes the other major component of most anti-malaria therapies [7,8]. Although the mechanisms of action of ACTs (artemisinin combination therapies) are still debated [9,10], most hypotheses invoke involvement of redox reactions in their cytotoxicity, since (i) the essential moiety in all therapeutically active forms of artemisinin is its endoperoxide ring [11], (ii) other components of common ACTs promote the accumulation of oxidative heme [12], (iii) erythrocyte mutations that increase oxidative stress within the parasitized RBC confer partial protection against malaria [13][14][15][16][17][18][19] (e.g., sickle cell, β-thalassemia, G6PDH (Glucose-6-phosphate dehydrogenase) deficiency, etc., and (iv) many other oxidizing drugs were found to exhibit antimalarial activity [20,21]. Taken together, these observations suggest that oxidative stress can be detrimental to the parasite, probably by creating an environment that is harmful to parasite maturation, proliferation, or egress.…”
Section: Introductionmentioning
confidence: 87%
“…Recently, we synthesized a series of 3-benzylmenadione derivatives [ 3 , 4 ], which were identified as potent antimalarial redox-active agents. Among these, the 3-[4-(trifluoromethyl)benzyl]-menadione (called plasmodione, Figure 1 ) showed the most promising ‘early lead’ features for drug optimization [ 5 , 6 ]. Mechanistic studies revealed that plasmodione may enter a cascade of redox reactions for drug bioactivation: in its oxidized state, the menadione derivative was proposed to be reduced by the NADPH-dependent glutathione reductases of the Plasmodium -parasitized erythrocytes; in its reduced state, the hydronaphthoquinone was shown to transfer 1e − to methemoglobin (Fe III ) (metHb), the major nutrient of the parasite [ 3 , 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%